La reconvención y su efecto jurídico en las sentencias dentro de los juicios ordinarios de prescripción extraordinaria adquisitiva de dominio en la Unidad Judicial Civil con sede en el cantón Riobamba durante el año 2015. - Parra Molina, Santiago Alejandro (2016)
The structure of this research is divided into five chapters: the first chapter deals with the guiding framework where the problem statement, its origin originates, as presented and how it behaves; the overall objective and specific objectives; justification and importance of the problem, where we observed that the present research work is feasible, innovative, original that will serve for lawyers and students of the career of law and citizens in general. In the second chapter the theoretical framework, where the instrument of signing through which doctrine, theories, concepts and bibliographical articles from codes, books, laws, and texts obtained was applied develops, building the theoretical, conceptual, legal part research and doctrinaire, this chapter is divided into five units, with their subunits; in the first unit talk about the extraordinary acquisitive prescription domain; in the second unit we talk about exceptions; in the third unit we talk about the counterclaim; in the fourth unit we talk about the legal effect of the counterclaim in the ordinary trials of extraordinary acquisitive prescription and practical analysis; in the fifth unit we see the hypothetical unit, hypothesis, variables, operationalization o variable. In the third chapter, we develop the methodological framework, through the analytical method through surveys Lawyers free exercise thereof; also interviews with the judges of the Civil Judicial Unit based in the canton Riobamba, the analytical method was applied to come to a critical and legal analysis to verify the hypothesis. In the fourth chapter, conclusions and recommendations set; Finally in the fifth chapter the literature, additional bibliography and Annexes.